Dielectric and gas transport properties of highly fluorinated polyimides blends. (August 2015) - Constantin, Catalin-Paul; Damaceanu, Mariana-Dana; Varganici, Cristian; Wolinska-Grabczyk, Aleksandra; Bruma, Maria
The physicochemical properties of highly fluorinated polyimide blends were studied in order to highlight the advantages of employing a high content of fluorine atoms to tailor the properties of polyimide materials. Thus, dynamo-mechanical analysis was used to evidence the physical phenomena taking place during heating. The trend of storage modulus, loss modulus and loss factor tangent with temperature during and after the α relaxation was explored. The dielectric spectroscopy was carried out to investigate the dielectric behaviour at different temperatures and frequencies and to evaluate the values of dielectric constant, dielectric loss and electrical resistance. The dielectric spectroscopy data were corroborated with the dynamo-mechanical analysis to highlight the sub-glass transitions encountered in these blend films. Dielectric loss diagrams showed sub-glass transitions in the form of γ and β relaxations mainly due to the segmental mobility of the polymer chain components. The gas separation performance of some of the investigated blends was assesed, and their ability to achieve simultaneously higher gas permeability and higher selectivity was demonstrated.